Avaliação de pulpectomias em molares decíduos utilizando diferentes materiais obturadores: ensaio clínico randomizado de 2 anos de acompanhamento - Sityá, Débora Santos (2018)
To maintain primary teeth in the oral cavity is very important to prevent damage in primary and permanent dentition, resulting in disturbance to development of the individual. In view of this, in trauma cases or extensive caries with pulp involvement, pulpectomy has been indicated. Different materials have been used in endodontic treatment to primary teeth, with different properties and variable clinical and radiographic results. Thus, this study aims to evaluate clinically and radiographically the pulpectomy in mandibular primary molars performed in the clinic of Pediatric Dentistry, Federal University of Santa Maria, comparing different pastes. Children with teeth presenting periapical or furcation injury was select to receive endodontic treatment, in line with inclusion and exclusion criteria. Procedures were performed according to a pre-established standard clinical protocol and using different root filling materials. The sample was randomly divided into three groups: Guedes-Pinto paste (Rifocort®, camphorated paramonochlorophenol (PMCC) and iodoform); Modified Guedes-Pinto paste (Nebacetin, PMCC and Iodoform); and Calcium hydroxide paste thickened with zinc oxide – (Calcium hydroxide P.A., propylene glycol and zinc oxide). Clinical and radiographic results were evaluated at 30, 60 and 90 days, 6 months, 1 year and 2 years after treatment, and no statistically significant difference was found between groups. The clinical assessment was performed regarding pain, swelling, fistula and/or mobility. The radiographic assessment was performed by a single, calibrated and blinded operator regarding the root filling material, according to pre-defined criteria to evaluation. Thus, the three pastes were considered viable for use in clinical practice generating a high survival rate after 24 months of follow-up.